2020
DOI: 10.21834/e-bpj.v5i13.2064
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Active Design for Technology-Driven Activities in Malaysia

Abstract: The youth nowadays focused more on electronic media technologies, which resulted in a decrease in physical activities and growing health problems. In combating this dilemma, exergaming is introduced. However, it needs to be incorporated with the environmental surrounding to be proactive. This paper intends to investigate the potentiality of implementing the active design strategy in technology-driven activities in Malaysia. The findings from existing exergaming case studies are synthesized into a design strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Moreover, physical activity has a positive impact on human health through cardiovascular health and combined built environment strategies to improve public health [96]. The primary dimensions describing how the built environment affects physical activity are infrastructure, aesthetic qualities, street network design, safety, exercise facilities, density, and intensity [97,98]. We can see that there is a strong linkage between the built environment and physical activity to achieve public health; as shown in Table 1, nine out of ten studies revealed that physical activity has a positive impact on student health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, physical activity has a positive impact on human health through cardiovascular health and combined built environment strategies to improve public health [96]. The primary dimensions describing how the built environment affects physical activity are infrastructure, aesthetic qualities, street network design, safety, exercise facilities, density, and intensity [97,98]. We can see that there is a strong linkage between the built environment and physical activity to achieve public health; as shown in Table 1, nine out of ten studies revealed that physical activity has a positive impact on student health.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple pieces of evidence showing that active design is an approach through which to enhance physical activity, create an active environment, and improve public health. Studies used active design guidelines [11], active design strategies [98], and the role of active design in improving physical health [99], as well as improving the physical activity environment [100]. Active design is an architectural intervention [101].…”
Section: Discussionmentioning
confidence: 99%